2017
DOI: 10.1093/ckj/sfx076
|View full text |Cite
|
Sign up to set email alerts
|

IgA nephropathy in Greece: data from the registry of the Hellenic Society of Nephrology

Abstract: BackgroundNatural history, predisposing factors to an unfavourable outcome and the effect of various therapeutic regimens were evaluated in a cohort of 457 patients with immunoglobulin A nephropathy (IgAN) and follow-up of at least 12 months.MethodsPatients with normal renal function and proteinuria <1 g/24 h as well as those with serum creatinine (SCr) >2.5 mg/dL and/or severe glomerulosclerosis received no treatment. Patients with normal or impaired renal function and proteinuria >1 g/24 h for >6 months rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Glucocorticoids are commonly used in the treatment of patients with IgA nephropathy as they improve the permeability of the glomerular membrane, facilitate urination, and reduce the level of urinary protein. Stangou et al [ 12 ] found that glucocorticoids also inhibited the inflammation and immune response in patients with IgA nephropathy. Methylprednisolone is a medium-acting glucocorticoid that regulates the cellular and humoral immunity, thereby enhancing the immune function of the patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are commonly used in the treatment of patients with IgA nephropathy as they improve the permeability of the glomerular membrane, facilitate urination, and reduce the level of urinary protein. Stangou et al [ 12 ] found that glucocorticoids also inhibited the inflammation and immune response in patients with IgA nephropathy. Methylprednisolone is a medium-acting glucocorticoid that regulates the cellular and humoral immunity, thereby enhancing the immune function of the patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we validated two risk-prediction models which accurately predict a 50% decline in eGFR or ESKD in patients with IgAN using the available data set from the national IgAN registry of the Greek society of Nephrology ( 8 ). From this data set, we extracted and used the clinical and histological information from patients with available MEST scores.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we included patients from the Greek Society of Nephrology IgAN registry ( 8 ). In this registry, patients with biopsy-proven IgAN are reported independently for research purposes from different nephrology departments across Greece.…”
Section: Methodsmentioning
confidence: 99%
“…If treated aggressively, C lesions were not associated with a worse outcome. 22 Similarly, Troyanov et al in their validation analysis also mentioned that M lesions may not be associated with proteinuria, and they questioned the validity of the M score. In addition, it has been the parameter with the worst reproducibility among pathologists.…”
Section: Validation Studiesmentioning
confidence: 99%